Implementing pull manufacturing in make-to-order environments - Almanei, Mohammed; Oleghe, Omogbai; Afy-Shararah, Mohamed; Salonitis, Konstantinos (IOS Press, 2022)
The demand for increasing product variety and customization has forced many companies to adopt a make-to-order (MTO) strategy. Traditional push-type MTO companies suffer from unstable demands, struggling to deliver on time, making them consider the utilization of pull systems to control production. In the present paper, an overview of pull systems in MTO environments is presented. Moreover, a discrete event simulation (DES) model of an MTO company in the printing and packaging industrial sector was developed and validated, in order to identify areas for improvement. DES was also used in order to evaluate the feasibility of implementing three types of pull systems: kanban, CONstant-Work-In-Process (CONWIP) and Paired Overlapping Loops of Cards with Authorizations (POLCA). The main performance indicators measured were the average WIP and the average throughput time of parts. The key findings of this project for the case study were: a) kanban is inapplicable for the current routing of parts; b) a CONWIP strategy improves the shop floor performance, but only when extra capacity is added to the extrusion workstation; c) production based on POLCA leads to the blockage of the system due to the existence of multi-routes and undirected routing.
Keywords: lean manufacturing; discrete event simulation; make-to-order